The Comparison of Elbow Extension and Elbow Flexion Movement Toward Forehand Accuracy of Court Tennis - Fajar Ari Widiyatmoko; Buyung Kusumawardhana; Muhammad Nur Ali Imran (UIR Press, 2021)
Some of the beginner athletes in UKM of court tennis in UPGRIS conduct swing on the forehand, striking slightly. Some when swinging with entirely straight arms, some are slightly bent. The study aims to investigate the differences between elbow extension and elbow flexion toward the accuracy level of forehand striking of court tennis. This research method uses a comparative design. The sample of this study is the tennis players of the students in PGRI University Semarang; the total is 7 people. The Hewitt Tennis Achievement Test is used for forehand striking instruments and dartfish software to determine the differences between the elbow movements and the analysis. An Independent t-test is used to find out the differences of the striking accuracy result. The results show the significant differences between elbow extension and elbow flexion with an average score of 22 and 63, with the significance value of a difference of 0.001. The conclusion is elbow flexion movement in the forwardswing step is better than elbow extension movement.